High Anxieties : Cultural Studies in Addiction - Redfield, Marc, 1958-; Brodie, Janet Farrell (Book collections on Project MUSE., 2002)
High Anxieties explores the history and ideological ramifications of the modern concept of addiction. Little more than a century old, the notions of "addict" as an identity and "addiction" as a disease of the will form part of the story of modernity.